Association between Parents' Consumption of Vegetables and Fruit and Students' Consumption of Vegetables and Fruit in Jakarta, Indonesia - Gina Amalia Chaerunnisa; Triyanti Triyanti (Indonesian Journal of Public Health Nutrition, 2023)
The increased risk of non-communicable diseases is still a problem in Indonesia, one of which is the lack of fruit and vegetable consumption. Available data show that although fruits and vegetables have a protective effect, the average consumption of fruits and vegetables is still below the recommended intake, especially in adolescents. This study aims to determine the description of fruit and vegetable consumption and to determine the factors of food parenting practices and other factors related to fruit and vegetable consumption in students of SMAN 37 Jakarta. This study uses a quantitative method with a cross-sectional study design conducted on 160 students with a simple random sampling method. Data was collected by filling out questionnaires and food record forms independently by respondents who were monitored online from July-August 2022. The results showed that 88.8 percent of respondents still consumed less fruit and vegetables (<400 grams/day). The bivariate results showed that there was a significant relationship between parents fruit and vegetable intake and fruit and vegetable consump-tion(p-value=0,000). It is recommended to provide nutrition education to adolescents and parents regarding knowledge related to the recommended consumption of fruits and vegetables, and the benefits and impacts of insufficient consumption of fruits and vegetables.